PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN DAN KEBIJAKAN DIVIDEN PADA NILAI PERUSAHAAN - Suffah, Roviqotus; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test the influence of profitability, leverage, firm size, and dividend policy in firm value. The independent variables are profitability, leverage, firm size, and dividend policy. Meanwhile, the dependent variable is firm value. The samples are 23 companies which are listed in LQ-45 index and the research periods are four years which is started from 2010 to 2013. The sample collection technique has been done by using purposive sampling. The financial statement data has been obtained from the Indonesia Stock Exchange (IDX). The analysis method has been done by using the multiple liniear regressions.The result of this research shows that (1) profitability has positive influence to firm value. High profitability can increase firm value; (2) leverage has positive influence to firm value. High leverage is used to control free cash flow; (3) dividend policy has positive influence to the firm value, due to the high dividend can return the capital of the investors; and (4) firm size does not have any influence to the firm value. Firm size does not have any influence since the object of the research is the LQ-45 index in which the companies which are listed in the index are companies which have high trade volume and capitalism, therefore the firm size does not influence the firm value.Keywords: Profitability, Leverage, Firm Size, Dividend Policy, Firm Value.